Reasons for conversion and adverse intraoperative events in Endoscopic Port Access™ atrioventricular valve surgery and minimally invasive aortic valve surgery. (14th February 2018) - van der Merwe, Johan; Van Praet, Frank; Stockman, Bernard; Degrieck, Ivan; Vermeulen, Yvette; Casselman, Filip
Abstract: OBJECTIVES: This study reports the factors that contribute to sternotomy conversions (SCs) and adverse intraoperative events in minimally invasive aortic valve surgery (MI-AVS) and minimally invasive Endoscopic Port Access™ atrioventricular valve surgery (MI-PAS). METHODS: In total, 3780 consecutive patients with either aortic valve disease or atrioventricular valve disease underwent minimally invasive valve surgery (MIVS) at our institution between 1 February 1997 and 31 March 2016. MI-AVS was performed in 908 patients (mean age 69.2 ± 11.3 years, 45.2% women, 6.2% redo cardiac surgery) and MI-PAS in 2872 patients (mean age 64.1 ± 13.3 years, 46.7% women, 12.2% redo cardiac surgery). RESULTS: A cumulative total of 4415 MIVS procedures (MI-AVS = 908, MI-PAS = 3507) included 1537 valve replacements (MI-AVS = 896, MI-PAS = 641) and 2878 isolated or combined valve repairs (MI-AVS = 12, MI-PAS = 2866). SC was required in 3.0% ( n = 114 of 3780) of MIVS patients, which occurred in 3.1% ( n = 28 of 908) of MI-AVS patients and 3.0% ( n = 86 of 2872) of MI-PAS patients, respectively. Reasons for SC in MI-AVS included inadequate visualization ( n = 4, 0.4%) and arterial cannulation difficulty ( n = 7, 0.8%). For MI-PAS, SC was required in 54 (2.5%) isolated mitral valve procedures ( n = 2183). Factors that contributed to SC in MI-PAS included lung adhesions ( n = 35, 1.2%), inadequate visualization ( n = 2, 0.1%), ventricular bleeding ( n = 3, 0.1%) and atrioventricular dehiscence ( n = 5, 0.2%). Neurological deficit occurred in 1 (0.1%) and 3 (3.5%) MI-AVS and MI-PAS conversions, respectively. No operative or 30-day mortalities were observed in MI-AVS conversions ( n = 28). The 30-day mortality associated with SC in MI-PAS ( n = 86) was 10.5% ( n = 9). CONCLUSIONS: MIVS is increasingly being recognized as the 'gold-standard' for surgical valve interventions in the context of rapidly expanding catheter-based technology and increasing patient expectations. Surgeons need to be aware of factors that contribute to SC and adverse intraoperative outcomes to ensure that patients enjoy the maximum potential benefit of MIVS and to apply effective risk reduction strategies that encourage safer and sustainable MIVS programmes.